2000
DOI: 10.1002/1529-0131(200006)43:6<1337::aid-anr16>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rolling neutrophils with antineutrophil cytoplasmic antibodies causes conversion to firm integrin‐mediated adhesion

Abstract: These findings support the concept that ANCA can directly activate neutrophils to become firmly adherent to vessel walls, where they may obstruct flow, initiate tissue damage, and contribute to pathogenesis of vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 29 publications
5
78
2
2
Order By: Relevance
“…CD18 blockade completely inhibits ANCA-induced neutrophil SO production, and CD11b blockade reduces ANCA-induced neutrophil adherence to platelets (8,41). Our finding that CD18 blockade diminished ANCA-induced Syk phosphorylation is consistent with these reports.…”
Section: Discussionsupporting
confidence: 90%
“…CD18 blockade completely inhibits ANCA-induced neutrophil SO production, and CD11b blockade reduces ANCA-induced neutrophil adherence to platelets (8,41). Our finding that CD18 blockade diminished ANCA-induced Syk phosphorylation is consistent with these reports.…”
Section: Discussionsupporting
confidence: 90%
“…Others have described arrest of rolling neutrophils in vitro in response to antineutrophil cytoplasmic antibodies and an in vivo shock reaction induced by antibodies against glycoprotein IIb/IIIa on platelets that are both Fc␥ receptor dependent. 26,27 In contrast to the above, our reaction was not Fc␥ receptor dependent ( Figure 5B). Antibody 2.4G2, at a dose which blocks Fc␥ receptors II and III, 27 failed to protect mice from RB6-8C5-induced microvascular arrest and death ( Figure 5B) or to prevent leukocyte depletion by RB6-8C5 (not shown).…”
Section: A Role For Selectins In Reactions Induced By Tnf-␣/rb6-8c5contrasting
confidence: 67%
“…Close proximity of the activated neutrophils to endothelial cells is required because the endothelial toxicity is inhibited by antibodies to ␤2 integrins (34). Savage and associates (35)(36)(37) showed that activation of neutrophils by ANCA causes integrin-and cytokine receptormediated adherence to cultured endothelial cells and transmigration across the endothelial layer. In addition, activation of neutrophils with ANCA causes a conformational change in ␤ integrins that enhances ligand binding (37).…”
Section: Neutrophil and Monocyte Activation By Anca In Vitromentioning
confidence: 99%